Mystical Practices and Amulets: The Views of Abdul Karim Amrullah in Minangkabau Culture - Fauzan Fauzan; Helfi Helfi; Fajrul Wadi; Dahyul Daipon (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research aims to explore the conception of magic and amulets during the time of Abdul Karim Amrullah, both in terms of concept and practice in Minangkabau. Magic and amulets are distinct aspects but closely related in Minangkabau culture. In the past, shamans primarily controlled magic, while amulets, as countermeasures, were held by tarekat scholars. Over time, with the integration of custom and Islam in Minangkabau's philosophy